2009
DOI: 10.1021/cr9000429
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Poled Organic Electro-optic Materials: State of the Art and Future Prospects

Abstract: Contents 42 4. Materials Processing Methodologies 44 4.1. Electric Field Poling 44 4.1.1. Conductivity Issues; Buffer Layers 45 4.1.2. Laser-Assisted Electric Field Poling 45 4.2. Lattice Hardening and Thermal Stability 46 5. Characterization Methods 46 5.1. Methods for Characterizing Molecular First Hyperpolarizability 46 5.2. Methods for Characterizing Electro-optic Activity 48 5.3. Characterization of Poling-Induced Order: VAPRAS 49 5.4. Characterization of Photochemical Stability 49 6. Devices and Applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
684
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 915 publications
(702 citation statements)
references
References 243 publications
5
684
0
3
Order By: Relevance
“…This phenomenon has found a number of applications in optical devices, such as electro-optic sensors based on ring microresonators, liquid crystal displays (LCDs), Q-switches for lasers, spatial light modulators, optical shutters, and variable density filters (Dalton et al, 2010). The three-dimensional (3D) hierarchical structures of CNCs at various scales and their ability to integrate other functional materials make CNC-based products promising candidates for electrical, electrochemical, and optical devices (Zheng et al, 2013).…”
Section: Biophotonic: "Green" Electro-optic Devicesmentioning
confidence: 99%
“…This phenomenon has found a number of applications in optical devices, such as electro-optic sensors based on ring microresonators, liquid crystal displays (LCDs), Q-switches for lasers, spatial light modulators, optical shutters, and variable density filters (Dalton et al, 2010). The three-dimensional (3D) hierarchical structures of CNCs at various scales and their ability to integrate other functional materials make CNC-based products promising candidates for electrical, electrochemical, and optical devices (Zheng et al, 2013).…”
Section: Biophotonic: "Green" Electro-optic Devicesmentioning
confidence: 99%
“…This type of molecules are highly targeted due to the easy tuning of the photophysical properties by small structural modifications. [1][2][3][4][5][6][7] The electronic arrangement of these compounds is based in an electron donor group linked to an electron acceptor group through a π-conjugated bridge, which leads to an efficient intramolecular charge transfer. Recent advances consists on the design of systems bearing heterocyclic π-bridges and/or the use of an electron rich or electron deficient heterocycle that acts as an adjuvant electron donor or acceptor group.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] To solve this challenge, one well-demonstrated molecular design strategy is to control the shape of chromophores by introducing additional isolation spacers into chromophores or locking chromophores inside 3D dendrimer shell, as suggested by Jen and co-workers and Dalton et al, which can generate effective site isolation effect to minimize undesirable intermolecular interactions at the molecular level, and hence improve the poling efficiency to enhance macroscopic NLO effects. [5,[9][10][11] In the past two decades, a wide variety of dendritic NLO materials with very promising macroscopic NLO effects have …”
mentioning
confidence: 99%
“…[5,[12][13][14][15] However, even for these dendritic NLO materials, both literature work [10,16] and our recent research work [14,15] have shown that the resultant macroscopic NLO properties are strongly correlated to their topological structure, due to the change in nanoscale environment around chromophores. For example, in 2010 we found that upon increasing generation of AB 2 -type dendrimers, the resultant NLO effects can be improved accordingly despite that the effective loading density of the chromophore moieties was also increased simultaneously, and thus the d 33 value of the fifth generation dendrimer can reach 193.1 pm V −1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation